Early-Onset Polycystic Kidney Disease In Two Juvenile Persian Kittens – A Comparative Study - Kwatra, Bhavuk (Journal of Applied Veterinary Science And Technology, 2025)
Background: Polycystic Kidney Disease (PKD) is a hereditary disorder frequently observed in Persian cats and related breeds. It is characterized by multiple cysts within the renal cortex and medulla, leading to progressive renal dysfunction and eventual chronic renal failure. Although PKD is typically diagnosed in adult cats, early-onset forms in juveniles are rarely reported. Clinical signs in young cats often resemble other systemic disorders such as urinary tract infections or gastroenteritis, making diagnosis challenging. Understanding the clinical presentation and progression of PKD in juvenile cats is essential for early detection and promoting responsible breeding programs to reduce genetic transmission. Purpose:  This study describes and compares two cases of early-onset PKD in juvenile Persian kittens that showed rapid progression toward chronic renal failure. It also highlights the importance of early genetic screening in high-risk breeds and evaluates the potential influence of homozygous mutations and secondary stressors on disease severity. Case(s):Two Persian kittens, Niharika (female, 1.5 kg) and Panther (male, 1.9 kg), presented as emergency cases at the Government Veterinary Clinic, Jabalpur, India, with systemic illness, inappetence, lethargy, and thermoregulatory instability. Both were unvaccinated and not dewormed. Despite intensive supportive therapy, both developed dehydration, fluctuating body temperature, and progressive clinical decline. Case Management: Despite aggressive treatment including fluid therapy, antibiotics, antiemetics, and nutritional support, both kittens died within six days of admission. The initial diagnosis of interstitial cystitis was later revised after poor response to standard care. Conclusion:  These cases demonstrate that autosomal dominant PKD in Persian cats can occur early and progress rapidly, likely due to homozygous mutations and secondary infections. Early genetic screening is critical for reducing hereditary renal disease in predisposed breeds.